STIMULASI PERKEMBANGAN SPIRITUALITAS LANSIA DI KELURAHAN PARAK GADANG TIMUR KOTA PADANG - Windy Freska; Dewi Eka Putri; Tiara Yalita (Jurnal Hilirisasi IPTEKS, 2020)
Currently the elderly population in Indonesia is 9.27%. The elderly experience some decline in various aspects of development such as biological, cognitive, psychological, social, and spiritual. The decline in development in the elderly will reduce the mental well-being of the elderly. This is also due to the lack of developmental stimulation in the elderly so that spiritual needs are needed as a developmental stimulation to improve the mental health welfare of the elderly. The purpose of the activity was to determine the effect of stimulating health education on the development of spirituality in the elderly in RW VIII, Parak Gadang Timur Village. Health education interventions to stimulate the development of spirituality are carried out by providing knowledge of spiritual aspects and lectures to respondents. Quasi experimental design before and after without a control group. Data were collected using a questionnaire on the spiritual aspects of the elderly to provide knowledge on spiritual aspects of the elderly and a Spirituality Orientation Inventery (SOI) to assess the spirituality of the elderly using the paired sample t test. From the results of the activity, it was obtained that the knowledge score of the elderly was an average before 0.72 points and after 2.27 points, and an increase in knowledge before and after was 1.56 points and showed a significant influence on the knowledge of the elderly before and after the intervention (p. <0.05). The description of the spiritual level of the elderly obtained the median value = 53 with the category ≥53 good. It is hoped that health care workers carry out scheduled spiritual activities to fulfill the spiritual needs of the elderly to maintain their health.